Glucocerebrosidase variant T369M is not a risk factor for Parkinson's disease in Sweden. (27th July 2022) - Ran, Caroline; Brodin, Lovisa; Gellhaar, Sandra; Westerlund, Marie; Fardell, Camilla; Nissbrandt, Hans; Söderkvist, Peter; Sydow, Olof; Markaki, Ioanna; Hertz, Ellen; Wirdefeldt, Karin; Svenningsson, Per
Highlights: T369M is not associated with PD in Sweden. T369M was not more common in Swedish patients with early onset. T369M might be more common in northern/Scandinavian populations. Abstract: Introduction: Genetic variants in the Beta-glucocerebrosidase gene ( GBA1 ) is a known risk factor for Parkinson's disease. The GBA1 mutations L444P, N370S and many other have been shown to associate with the disease in populations with diverse background. Some GBA1 polymorphisms have a less pronounced effect, and their pathogenicity has been debated. We have previously found associations with L444P, N370S and E326K and Parkinson's disease in Sweden. Method: In this study we used pyrosequencing to genotype the T369M variant in a large Swedish cohort consisting of 1, 131 patients with idiopathic Parkinson's disease, and 1, 594 control subjects to evaluate the possibility of this variant conferring an increased risk for Parkinson's disease. Results: The minor allele frequency was 2.15% in patients and 1.76% in controls. Statistical analysis showed that there was no significant difference in allele frequency between patients and control subjects, p-value 0.37, Odds Ratio 1.23 with a 95% confidence interval of 0.82–1.83. Conclusion: Our results suggest that T369M is not a risk factor for Parkinson's disease in the Swedish population.